Distributed blockchain assisted secure data aggregation scheme for risk-aware zone-based MANET - V R. Sugumaran; E. Dinesh; R. Ramya; Elangovan Muniyandy (Scientific Reports)
Abstract This research work proposes a Distributed Blockchain-Assisted Secure Data Aggregation (Block-DSD) technique for MANETs, ensuring high security and energy efficiency in disaster management scenarios. A Zone-based Clustering Approach (ZCA) is employed to segment the network into secure zones, with optimal Cluster Heads (CHs) selected using the Artificial Neuro-Fuzzy Inference System (ANFIS). Data aggregation is secured through a Two-Step Secure (STS) method and Elliptic Curve Cryptography (ECC), while optimal routing is achieved using the Improved Elephant Herd Optimization (IEHO) algorithm. Simulations using ns-3.25 demonstrate a 97% Packet Delivery Ratio (PDR), 20% lower energy consumption compared to existing methods, and minimal latency of 0.0012 s for emergency data, validating the proposed framework’s efficiency and robustness in dynamic MANET environments.